2018
DOI: 10.3390/ijms19113396
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-Expression of KRT5 and KRT20 Defines Distinct Prognostic Subgroups of Muscle-Invasive Urothelial Bladder Cancer Correlating with Histological Variants

Abstract: Recently, muscle-invasive bladder cancer (MIBC) has been subclassified by gene expression profiling, with a substantial impact on therapy response and patient outcome. We tested whether these complex molecular subtypes of MIBC can be determined by mRNA detection of keratin 5 (KRT5) and keratin 20 (KRT20). Reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) was applied to quantify gene expression of KRT5 and KRT20 using TaqMan®-based assays in 122 curatively treated MIBC patients (median age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 45 publications
4
41
0
1
Order By: Relevance
“…Also, KRT5 is highly upregulated in basal and KRT20 in luminal subtype in BLCA [6]. qPCR-based molecular subtyping of BLCA by KRT5 and KRT20 mRNA expression is a method associated with the survival of patients with MIBC [43]. It is confirmed that KRT5 and KRT20 showed significant association with ANLN and TLE2 in the Mannheim cohort.…”
Section: Discussionmentioning
confidence: 62%
“…Also, KRT5 is highly upregulated in basal and KRT20 in luminal subtype in BLCA [6]. qPCR-based molecular subtyping of BLCA by KRT5 and KRT20 mRNA expression is a method associated with the survival of patients with MIBC [43]. It is confirmed that KRT5 and KRT20 showed significant association with ANLN and TLE2 in the Mannheim cohort.…”
Section: Discussionmentioning
confidence: 62%
“…The keratin 5 gene, KRT5, is amongst the upregulated genes in urine from bladder cancer patients compared to healthy volunteers. The presence of KRT5 mRNA in tumor tissue has been studied to subclassify muscle-invasive bladder cancers according to therapy response and patient outcome 38 . In CSF from glioblastoma patients, only 2 mRNAs are significantly upregulated compared to CSF from hydrocephalus patients.…”
Section: Assessment Of the Tissues Of Origin And Deconvolution Of Panmentioning
confidence: 99%
“…A reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR)-based assessment was used for the objective quantification of FOXA1, GATA3, and AR mRNA expression, as previously described and performed with KRT5 and KRT20 [22,25]. In brief, RNA was extracted from a single 10-µm section of formalin-fixed paraffin embedded (FFPE) routine tissue using a commercially available bead-based extraction method (Xtract ® kit; STRATIFYER Molecular Pathology GmbH, Cologne, Germany).…”
Section: Assessment Of Mrna Expression By Rt-qpcrmentioning
confidence: 99%
“…One-step RT-qPCR was applied for the relative quantification of the mRNA expression of the genes of interest (FOXA1, GATA3 and AR) as well as the reference gene (Calmodulin 2 (CALM2)) by gene-specific TaqMan ® -based assays using the SuperScript III PLATINUM One-Step, quantitative RT-PCR System (Invitrogen, Karlsruhe, Germany) on a Stratagene Mx3005p system (Agilent Technologies, Böblingen, Germany) with 30 minutes at 50 • C, two minutes at 95 • C, followed by 40 cycles of 15 seconds at 95 • C and 30 seconds at 60 • C as described previously [22,25].…”
Section: Assessment Of Mrna Expression By Rt-qpcrmentioning
confidence: 99%
See 1 more Smart Citation